Assessing teachers’ capacity in reading instruction: Evidence from Laparay Elementary School - Mark Anthony Ignacio (Eureka: Journal of Educational Research, 2025)
This qualitative case study examined the reading instruction capacity of six teachers at Laparay Elementary School, a remote and resource-constrained public school in Talusan District, Philippines. Data were collected through semi-structured interviews and analyzed using thematic analysis informed by an inductive approach. Findings revealed that teachers demonstrated strengths in fostering engaging and supportive reading environments through phonics instruction, fluency practice, comprehension strategies, and the use of culturally relevant texts. However, teachers also faced persistent challenges related to diverse learner reading levels, limited attention spans, gaps in foundational skills, scarcity of instructional materials, and insufficient home literacy support. Teachers addressed these challenges by applying developmentally appropriate strategies, differentiated instruction, and assessment-driven instructional adjustments. The study highlights the need for targeted professional development, adequate instructional resources, and community-based literacy initiatives to strengthen teacher capacity and improve reading outcomes in rural elementary schools.